DOI for the crop-specific ontologies of Crop Ontology - Arnaud, Elizabeth; Laporte, Marie-Angelique (2023)
The Crop Ontology compiles crop-specific trait ontologies developed by a community of ontology curators, crop experts, data scientists, database developers, etc. The ontologies are published online under the CC-by-40 license in the the Crop ontology website (cropontology.org). Each crop-specific ontologies is an intellectual asset compiling the knowledge of researchers on traits contributing to the crop phenotypes. Therefore, a solution was proposed to the CO Community of curators to allocate to each ontology a DOI (Digital Object Identifier) with an adequate citation. Each ontology is recorded in the open science repository called Zenodo that enables the management of versions and their DOIs. The presentation poposes a summary of the answers collected with the survey launched in 2023 about DOIs and exposes the proposition that was selected by the community.